Hexagonal boron nitride powder and method for producing the same
Patent Information
- Application Number
- JP2023569237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-01
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-12-01
AI Technical Summary
【0010】 本発明の六方晶窒化ホウ素粉末は、粒度分布がシャープで粒子径が揃っており、化粧料に好適に用いることができる。さらに本発明の六方晶窒化ホウ素粉末を含む化粧料は、滑り性が良く、しっとり感(肌なじみ)が良く、ざらつきが少ない。本発明の窒化ホウ素粉末の製造方法によれば、粒度分布がシャープで粒子径が揃った六方晶窒化ホウ素粉末を製造することが出来る。
Smart Images

Figure 0007936820000001
Abstract
Description
[Technical Field]
[0001] This invention relates to hexagonal boron nitride powder (hereinafter sometimes abbreviated as boron nitride powder or h-BN powder). More specifically, it relates to hexagonal boron nitride powder suitable for use in cosmetics and a method for producing the same. [Background technology]
[0002] Inorganic materials such as talc, mica, and kaolin, and resin materials such as nylon powder and polyethylene powder have been used as cosmetics. However, their usability and stability have not always been satisfactory. For example, inorganic materials such as talc, mica, and kaolin have catalytic activity, which is said to cause deterioration of fragrances and oils, leading to unpleasant odors. Resin materials such as nylon powder and polyethylene powder, while chemically stable, have the problem of poor moldability. Therefore, hexagonal boron nitride, which has a flattened shape and superior lubricity compared to other materials, has been used as a pigment in cosmetics. Cosmetics are the base on which coloring pigments are dispersed, and they greatly affect the feel of the product, such as its spreadability (the property of being able to apply smoothly to the skin surface) and its longevity (the property of maintaining the applied state on the skin).
[0003] Patent Document 1 describes a boron nitride powder that is produced by reacting boric acid, urea, and boron carbide in a predetermined ratio of oxygen to carbon, and consists of a plate-like aggregate in which primary particles having a predetermined average major diameter and thickness are stacked. Patent Document 2 describes a hexagonal boron nitride powder that can improve lubricity and reduce roughness, having a predetermined average particle size, maximum particle size, specific surface area, predetermined graphitization index, average friction coefficient, and variation value of the average friction coefficient. Patent Document 2 also describes a method for producing hexagonal boron nitride powder by defining first and second firing conditions. Patent Document 3 describes how the property of a cosmetic product to remain on the skin for an extended period is closely related to the amount of oil absorbed by the constituent powders of the cosmetic, and proposes a boron nitride powder having a predetermined water penetration rate and oil absorption capacity. The boron nitride powder described in Patent Document 3 is manufactured by performing a two-stage heat treatment on boric acid, urea, and boron carbide.
[0004] Patent Document 4 proposes a boron nitride powder suitable for cosmetics, which maintains a moderate level of slipperiness while exhibiting excellent tactile properties such as "moist" and "slimy," and wherein the amount of eluted boron, average particle size, and content of particles of a specific particle size are below predetermined values. Patent Document 4 also describes the average coefficient of friction and the variation value of the average coefficient of friction of this boron nitride powder. Furthermore, Patent Document 4 describes a method for producing boron nitride powder by two-stage calcination, pulverization, and washing. Patent Document 5 proposes a hexagonal boron nitride powder capable of realizing a resin sheet with high thermal conductivity and high dielectric strength, wherein the hexagonal boron nitride powder has a predetermined specific surface area, major axis of primary particles, and aspect ratio. Patent Document 5 also describes a method for producing hexagonal boron nitride powder by heating boron oxide, an organic compound containing nitrogen, and lithium carbonate in a predetermined weight ratio. Patent Document 6 describes a method for producing hexagonal boron nitride powder with a low aspect ratio, which involves crushing a raw material powder containing hexagonal boron nitride particles having an aspect ratio within a predetermined range and hexagonal boron nitride particles having an aspect ratio exceeding a predetermined value, by means of substantially not involving the pulverization of primary particles. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2012-176910 [Patent Document 2] Japanese Patent Publication No. 2018-165241 [Patent Document 3] International Publication No. 2014 / 049956 [Patent Document 4] International Publication No. 2019 / 172440 [Patent Document 5] International Publication No. 2020 / 179662 [Patent Document 6] International Publication No. 2021 / 085223 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] The object of the present invention is to provide a cosmetic product containing hexagonal boron nitride powder that has good slipperiness, a moist feel (good skin compatibility), and low roughness. Another object of the present invention is to provide a method for producing the boron nitride powder. [Means for solving the problem]
[0007] Therefore, the inventors have discovered that when producing hexagonal boron nitride powder by a reduction nitridation method in which a raw material mixture is heated in a nitrogen atmosphere, if a BN seed crystal produced by the melamine method is present as a seed crystal, boron nitride powder with uniform particle size can be produced. Such boron nitride powder with uniform particle size has good slipperiness, a moist feel (comfort with the skin), and less roughness, thus completing the present invention.
[0008] In other words, the present invention encompasses the following inventions. 1. In the volume-based cumulative distribution of particle size (a) measured by laser diffraction / scattering without ultrasonic treatment, the particle size of D95 is 70 μm or less, the coefficient of dynamic friction (MIU) is 0.50 or less, and the variation value of the coefficient of dynamic friction (MMD) is 0.005 or less. The D95 is the 95th percentile value of the volume-based cumulative distribution of particle size (a) in the particle size distribution curve. In the volume-based cumulative particle size distribution (b) measured by laser diffraction / scattering after ultrasonic treatment, the average particle size (D50) is 3 to 15 μm, (D90-D10) / D50 is 1.30 or less, the content of coarse particles exceeding 3 times D50 is 2.0 volume% or less, and D10, D50, and D90 are the cumulative 10th percentile, 50th percentile, and 90th percentile values, respectively, in the volume-based cumulative particle size distribution (b) of the particle size distribution curve. A hexagonal boron nitride powder characterized by the following features. 2. Hexagonal boron nitride powder as described in item 1 above, for use in cosmetics. 3. A cosmetic composition containing the hexagonal boron nitride powder described in item 1 or 2 above. [Effects of the Invention]
[0010] The hexagonal boron nitride powder of the present invention has a sharp particle size distribution and uniform particle size, making it suitable for use in cosmetics. Furthermore, cosmetics containing the hexagonal boron nitride powder of the present invention have good slipperiness, a good moist feel (compatibility with skin), and less roughness. The method for producing the boron nitride powder of the present invention makes it possible to produce hexagonal boron nitride powder with a sharp particle size distribution and uniform particle size. [Modes for carrying out the invention]
[0011] <Hexagonal boron nitride powder> <d95> The boron nitride powder of the present invention has a D95 particle diameter in the volume-based cumulative particle size distribution (a) measured by a laser diffraction / scattering method without ultrasonic treatment of 70 μm or less, preferably 65 μm or less, and more preferably 60 μm or less. D95 is a value for the boron nitride powder that has not been subjected to ultrasonic treatment. When D95 exceeds the above value, the properties required for cosmetics such as slipperiness, moist feel, and graininess are deteriorated. In the present invention, D95 in the case where ultrasonic treatment is not performed means the 95% cumulative value in the volume-based cumulative particle size distribution (a) on the particle size distribution curve.
[0012] <MIU and MMD> As a method for quantifying the slipperiness of cosmetics, there is MIU (dynamic friction coefficient). A smaller MIU value indicates that the cosmetic has more excellent slipperiness. In addition, as a method for quantifying the graininess of cosmetics, there is MMD (variation value of dynamic friction coefficient). A smaller MMD value indicates that the graininess of the cosmetic is lower. The dynamic friction coefficient (MIU) of the boron nitride powder of the present invention is 0.50 or less, preferably 0.46 or less, and more preferably 0.43 or less. By setting the MIU of the boron nitride powder to 0.50 or less, the slipperiness of the cosmetic can be further improved. The variation value (MMD) of the dynamic friction coefficient of the boron nitride powder of the present invention is 0.005 or less, preferably 0.004 or less, and more preferably 0.003 or less. By setting the MMD of the boron nitride powder to 0.005 or less, the graininess of the obtained cosmetic can be suppressed, and the use feel of the obtained cosmetic can be improved.
[0013] "MIU (dynamic friction coefficient)" and "MMD (variation value of dynamic friction coefficient)" in the present specification are dimensionless numbers measured using a friction tester (manufactured by Kato Tech Co., Ltd., trade name: KES-SE). Specifically, boron nitride powder is placed on artificial leather simulating human skin (manufactured by Idemitsu Techno Fine Co., Ltd., trade name: Sapurare PBZ13001 BK) at 0.5 mg / cm 2 spread it thinly so as to satisfy the condition, then place the sensor part (10 mm square silicon) of the friction tester thereon, and MIU and MMD can be measured. The measurement conditions for the friction tester are set as follows: sensitivity: H, test table moving speed: 1 mm / sec, static load: 25 gf. The measurement is performed once. The sample preparation (spreading and coating the boron nitride powder on the artificial leather) and the measurement with the friction tester are repeated 5 times, and the average value of the 5 obtained measurement results is defined as the MIU and MMD of the boron nitride powder.
[0014] <Primary Particle> The hexagonal boron nitride powder of the present invention includes primary particles and secondary particles formed by aggregation of primary particles. Therefore, in order to measure the particle size of the primary particles, it is necessary to perform measurement in a state where the secondary particles are almost completely broken by ultrasonic treatment under specific conditions to leave only the primary particles. In the present invention, particles subjected to ultrasonic treatment under specific conditions may be referred to as primary particles. The ultrasonic treatment is performed by dispersing 1 g of the hexagonal boron nitride powder of the present invention in 20 g of ethanol using an ultrasonic homogenizer. The particle size distribution of the primary particles is a volume-based cumulative particle size distribution (b) measured by a laser diffraction / scattering method. When the boron nitride powder of the present invention is incorporated into a cosmetic and applied to the skin, the boron nitride powder is crushed and slides under the force during application (shear force between the finger and the skin), so the physical properties as primary particles are important. Therefore, the present invention also focuses on the particle size distribution of the primary particles.
[0015] The average particle diameter (D50) of the primary particles is 3 to 15 μm, preferably 4 to 12 μm. Here, the average particle diameter (D50) refers to the value at 50% cumulative on a volume basis. When the D50 of the primary particles of the boron nitride powder is less than 3 μm, the slipperiness becomes insufficient. When the D50 average particle diameter of the primary particles exceeds 15 μm, the slipperiness is excessively high, so that the tactile sensations of the cosmetic such as "moist" and "slimy" are impaired, and the glaring appearance of the boron nitride powder becomes strong, which is not preferable as a raw material for cosmetics.
[0016] The (D90-D10) / D50 ratio of the primary particles is 1.30 or less, preferably 1.20 or less, and more preferably 1.10 or less. A smaller (D90-D10) / D50 ratio indicates a sharper particle size distribution and more uniform particle size. A smaller value results in better slipperiness and a smoother, more "moist" feel. While there is no particular lower limit, it is generally 0.60 or higher for boron nitride powder. The primary particles contain coarse particles that are more than three times the amount of D50, with a content of 2.0% by volume or less, preferably 1.8% by volume or less, and more preferably 1.3% by volume or less. The lower the coarse particle content, the more "moist" the texture will be, and the less roughness will be suppressed.
[0017] In the present invention, D10, D50, and D90 of the primary particles refer to the cumulative 10th percentile (D10), cumulative 50th percentile (D50), and cumulative 90th percentile (D90) values in the cumulative distribution of volume-based particle size (b) in the particle size distribution curve, respectively.
[0018] The particle size distribution curve is calculated from the volume-based particle size distribution measured using a laser diffraction / scattering particle size distribution analyzer after dispersing the measurement powder in ethanol and subjecting it to ultrasonic treatment. For the ultrasonic treatment, 20g of ethanol is added as a dispersion medium to a 50mL screw-cap bottle, 1g of the measurement powder is dispersed in the ethanol, and then ultrasonic treatment is performed using an ultrasonic homogenizer (Branson, product name: SFX250) with the tip (20kHz microchip 1 / 4 inch) positioned 1-5mm from the bottom of the screw-cap bottle, at an amplitude of 40% for 20 minutes.
[0019] <Cosmetics> The above-mentioned hexagonal boron nitride powder can be used in cosmetics. The present invention encompasses cosmetics containing the above-mentioned hexagonal boron nitride powder. Examples of cosmetics include foundations (powder foundations, liquid foundations, cream foundations), face powders, point makeup, eyeshadows, eyeliners, nail polishes, lipsticks, blushes, and mascaras. The cosmetics of this disclosure are particularly well suited to powder foundations and face powders among the above-mentioned cosmetics.
[0020] The content of the boron nitride powder in the cosmetic composition is preferably 0.1 to 70% by mass, and more preferably 1 to 30% by mass, based on the total amount of the cosmetic composition. Other ingredients include pigments such as red iron oxide, yellow iron oxide, black iron oxide, titanium dioxide, silica, aluminum hydroxide, and mica; esters such as diisostearyl malate and glyceryl tri-2-ethylhexanoate; and oils such as petrolatum. Other ingredients include talc, silicone powder, urethane powder, methylparaben, and sodium dehydroacetate.
[0021] <Method for producing hexagonal boron nitride powder> The present invention relates to a method for producing boron nitride powder, which includes a reduction nitridation step in which a raw material mixture is heated in a nitrogen atmosphere in the presence of a seed crystal (S).
[0022] <Seed crystal (S)> The seed crystal (S) is a hexagonal boron nitride powder (hereinafter sometimes referred to as BN seed crystal) produced by the melamine method. The melamine method is a method for producing BN seed crystals by nitriding an oxygen-containing boron compound using a nitrogen-containing organic compound (described later) as a nitrogen source. BN seed crystals obtained using a nitrogen-containing organic compound other than melamine can also be suitably used.
[0023] The seed crystal (S) has a specific surface area of 5 m² as measured by the nitrogen adsorption BET single-point method. 2 Particles of 5 m² or more are preferably used. Generally, the larger the primary particle, the smaller the specific surface area, and a specific surface area of 5 m² is preferable. 2 Particles smaller than / g may be equal to or larger than the primary particles of the target BN seed crystal and are therefore undesirable as seed crystals (S). Furthermore, for BN seed crystals with extremely small primary particle diameters, the particle size distribution may not be accurately measured by laser diffraction / scattering; therefore, the primary particle diameter of seed crystals (S) is determined by their specific surface area. The specific surface area of the seed crystal (S) is 5 m². 2 It is preferable that it be 8m or more / g. 2 More preferably 10m / g or more, 2 A value of 1 / g or more is even more preferable. There is no particular upper limit, but since it becomes difficult to handle if it is too large, it is preferably 200m. 2 / g or less, particularly preferably 100m 2 It is less than / g.
[0024] Seed crystals (S) can be produced by heating a raw material mixture containing an oxygen-containing boron compound and a nitrogen-containing organic compound under a nitrogen atmosphere. Examples of oxygenated boron compounds include boric acid, boric anhydride (boron oxide), metaboric acid, perboric acid, hypoboric acid, sodium tetraborate, and sodium perborate. Examples of nitrogen-containing organic compounds include melamine, ammeline, cyandiamide, and urea.
[0025] The raw material mixture may contain an oxygenated alkaline earth metal compound. Examples of oxygenated alkaline earth metal compounds include magnesium carbonate (MgCO3), calcium carbonate (CaCO3), and calcium oxide (CaO). Furthermore, two or more of these may be used in combination. The heating temperature is preferably 500 to 1200°C, more preferably 600 to 1100°C, and even more preferably 650 to 1000°C. The lower the heating temperature, the more uniform the primary particle size of the resulting seed crystal (S) tends to be. The heating time is preferably 5 to 20 hours, more preferably 6 to 15 hours. The longer the heating time, the more uniform the primary particle size of the resulting seed crystal (S) tends to be.
[0026] In the raw material mixture for seed crystal (S) production, the elemental ratio of boron / nitrogen (B / N) is preferably 0.2 to 1, more preferably 0.25 to 0.5. The manufactured seed crystal (S) may be used as is, but it is preferable to crush it using a jet mill or millstone crusher to facilitate uniform mixing with other raw materials used in the reduction nitriding process. Furthermore, it may be purified by acid washing, filtration, water washing and drying before use.
[0027] Seed crystals (S) are produced using the melamine method to obtain BN seed crystals with uniform particle size. In the melamine method, the reaction temperature (boron nitride formation temperature) is low, between 500 and 1200°C, which is presumed to be the reason why BN seed crystals with uniform particle size can be obtained. On the other hand, in the reductive nitriding method, the reaction temperature is high, above 1400°C, so boron nitride formation and crystal growth proceed simultaneously, making it difficult to obtain BN seed crystals with uniform particle size. In the reduction-nitriding process, particle growth occurs with seed crystals (S) as nuclei. Therefore, if the particle size of the seed crystals (S) is uniform, the primary particle size of the boron nitride powder is also more likely to be uniform.
[0028] <Reduction Nitride Process> The reduction nitriding process is a process in which a raw material mixture is heated in a nitrogen atmosphere. The raw material mixture contains an oxygenated boron compound, an oxygenated alkaline earth metal compound, a carbon source compound, and boron nitride powder produced by the melamine process as a seed crystal (S).
[0029] <Oxygen-containing boron compounds> Examples of oxygen-containing boron compounds include diboron trioxide (boron oxide), diboron dioxide, tetraboron trioxide, tetraboron pentoxide, borax, or anhydrous borax, with diboron trioxide (B2O3) being particularly preferred. Using diboron trioxide as the boron compound is industrially beneficial because it allows the use of inexpensive raw materials. Two or more boron compounds may be used in combination.
[0030] <Oxygen-containing alkaline earth metal compounds> Examples of oxygen-containing alkaline earth metal compounds include oxides or carbonates of alkaline earth metals such as calcium and magnesium. Specifically, magnesium oxide, calcium oxide, magnesium carbonate, calcium carbonate, magnesium bicarbonate, calcium bicarbonate, magnesium hydroxide, calcium hydroxide, magnesium nitrate, calcium nitrate, magnesium sulfate, calcium sulfate, magnesium phosphate, calcium phosphate, magnesium oxalate, calcium oxalate, etc. can be used. By using carbon oxides such as magnesium carbonate and calcium carbonate as oxygen-containing alkaline earth metal compounds, carbon dioxide gas is generated during the heating process, creating pores inside the mixed raw material layer, which allows nitrogen gas to easily penetrate the mixed raw material layer, and the reduction-nitridation reaction proceeds more efficiently. Two or more oxygen-containing alkaline earth metal compounds may be used in combination.
[0031] <Carbon source compounds> As carbon source compounds, amorphous carbon such as carbon black, activated carbon, and carbon fiber, as well as crystalline carbon such as diamond, graphite, and nanocarbon, and pyrolysis carbon obtained by thermally decomposing monomers and polymers can be used. When carbon black is used as the carbon source compound, hexagonal boron nitride powder with uniform particle size can be obtained in particular.
[0032] By using a carbon source compound, a reductive nitridation reaction occurs in the subsequent heating step, and the newly generated boron nitride contributes to the growth of seed crystals (S). If a carbon source compound is not used, the seed crystals (S) dissolve in the oxygen-containing boron compound, and the dissolved seed crystals (S) contribute to the growth of other seed crystals (S). In this case, if the particle size is large, the primary particle size of the resulting hexagonal boron nitride powder will not be sufficiently uniform. The reason is not clear, but in order to obtain boron nitride powder with sufficiently uniform primary particle size, it is necessary to use a carbon source compound and induce a reductive nitridation reaction.
[0033] <Composition ratio of raw material mixture in the reduction nitriding process> The atomic ratio (B / C ratio) of the boron atom (B) of the oxygen-containing boron compound and the carbon atom (C) of the carbon source compound in the raw material mixture in the reduction nitridation step is preferably 0.70 to 2.00, more preferably 0.71 to 1.70, and still more preferably 0.72 to 1.30. By blending the carbon source compound such that the B / C ratio falls within the above range, a boron nitride powder with uniform primary particle diameters can be obtained. If the carbon source compound is too small, the primary particle diameters are difficult to be uniform, and if the carbon source compound is too large, unreacted carbon remains as black foreign matter in the boron nitride powder, which is not preferable.
[0034] The content of the oxygen-containing alkaline earth metal compound in the raw material mixture is such that the molar ratio (MO / B₂O₃) of the oxygen-containing alkaline earth metal compound (MO; M is an alkaline earth metal) in terms of oxide to the oxygen-containing boron compound is preferably 0.01 to 1.0, more preferably 0.03 to 0.8, still more preferably 0.05 to 0.6, and particularly preferably 0.08 to 0.4. The oxygen-containing alkaline earth metal compound functions as a grain growth aid for boron nitride particles, and by blending the oxygen-containing alkaline earth metal compound such that MO / B₂O₃ falls within the above range, it is possible to obtain a boron nitride powder having a target primary particle diameter, good slipperiness, and less roughness.
[0035] The boron atom (B of the boron nitride powder (BN seed crystal) of the seed crystal (S) S ) and the carbon atom (C) of the carbon source compound have an atomic ratio (B S / C ratio) of preferably 0.01 to 13, more preferably 0.1 to 10, and still more preferably 0.2 to 8. By blending the seed crystal (S) such that the B S / C ratio falls within the above range, a boron nitride powder with uniform primary particle diameters can be efficiently obtained. If the amount of the seed crystal (S) is too small, the effect as the seed crystal cannot be obtained. If the amount of the seed crystal (S) is too large, the primary particles are difficult to be uniform, which is disadvantageous in terms of productivity.
[0036] <Heating step> The reduction nitriding process is a process in which a raw material mixture is heated under a nitrogen atmosphere. The reaction when producing boron nitride powder (BN) using boron oxide (B2O3) or an oxygen-containing boron compound that decomposes to boron oxide (B2O3) and carbon (C) or pyrolysis carbon that decomposes to carbon (C) is as follows. B2O3 + 3C + N2 → 2BN + 3CO
[0037] This reaction starts at approximately 1400°C or higher. The reaction temperature is preferably 1400-1600°C, more preferably 1450-1580°C. If the reaction temperature is too low, the reaction time will be long, and if the reaction temperature is too high, the primary particle size of the boron nitride powder will not be uniform. The holding time is preferably 1-10 hours, more preferably 2-8 hours. If the holding time is too short, the primary particle size of the boron nitride powder will not be uniform.
[0038] After the reaction, the heating temperature is increased to 1700-2100°C. As the temperature rises, the crystallization of boron nitride particles progresses, and the primary particle size increases. The maximum temperature is more preferably 1730-2000°C, and even more preferably 1750-1950°C. If the maximum temperature is too low, the primary particles of boron nitride powder will not grow to a size suitable for use in cosmetics, and if the maximum temperature is too high, they will grow excessively beyond a size suitable for use in cosmetics. The post-reaction heating is preferably maintained at a temperature between 1700 and 2100°C (preferably 1730°C to 2000°C, and more preferably 1750°C to 1950°C) for at least 0.5 hours (preferably 1 hour). If the holding time is too short, it becomes difficult to obtain reproducibility of the primary particle size of the boron nitride powder. However, if the holding time is too long, productivity decreases, so the holding time at the above temperature is preferably 7 hours or less, and more preferably 4 hours or less.
[0039] Nitrogen gas is necessary as a nitrogen source in the reductive nitriding reaction, and it is preferable to supply it by circulating it within the heating furnace. The nitrogen gas circulation path should be designed so that the circulating nitrogen gas comes into contact with the raw material mixture placed in the heating furnace (for example, circulating in the space above the raw material mixture layer). The nitrogen gas flow rate is preferably 0.1 to 20 L / min per 1 kg of mixed raw material, more preferably 0.2 to 15 L / min, and even more preferably 0.3 to 10 L / min. If there is too little nitrogen gas, the reductive nitriding reaction will not be completed, and unreacted carbon will remain as black foreign matter in the boron nitride powder, which is undesirable. If there is too much nitrogen gas, the thermal efficiency will decrease, which is also undesirable.
[0040] The raw material mixture can be filled into a carbon container, a boron nitride-coated carbon container, a boron nitride sintered body container, etc., and placed in a heating furnace. The shape of the container is preferably such that it does not hinder contact between the raw material mixture and the flowing nitrogen gas. The raw material mixture is preferably filled into the container to a height of 1 to 20 cm. If the packed layer is too low, productivity will decrease, and if the packed layer is too high, the reaction of the raw material mixture at the bottom of the container will not proceed, and unreacted carbon will remain in the boron nitride powder as black foreign matter, which is undesirable. The packed layer height of the raw material mixture is more preferably 2 to 15 cm, and even more preferably 3 to 10 cm.
[0041] <Washing process> The reaction product obtained in the reduction-nitriding process contains impurities other than hexagonal boron nitride, such as unreacted raw materials (B2O3, CaO). By removing these impurities through acid washing, high-purity hexagonal boron nitride powder suitable for cosmetic applications can be obtained. The method of acid washing is not particularly limited, and known methods can be applied without restriction. For example, one method involves manually dissolving the reaction product obtained in the reduction-nitriding step and placing it in a container, adding 3 to 10 times the amount of dilute hydrochloric acid (5 to 20% by mass HCl) to the reaction product, and stirring for 1 to 20 hours.
[0042] After acid washing, the material is washed with pure water to remove the acid. To avoid secondary contamination with impurities, pure water with an electrical conductivity of 1 mS / m or less can be used. The washing method involves filtering the acid used for acid washing, adding the same amount of pure water as the acid used, and filtering again. Furthermore, washing and filtering with pure water is repeated until the filtrate becomes neutral. In particular, when using hexagonal boron nitride powder in cosmetics, it is desirable that it conform to the 2021 Quasi-Drug Raw Material Standards, which include specifications such as purity of 95% or higher, pH of 5.0 to 8.0, and eluted boron content of 20 ppm or less. Therefore, it is necessary to wash the powder to satisfy these requirements.
[0043] If solid-liquid separation is performed after washing and then drying, there are no particular limitations on the method of solid-liquid separation. For example, decantation, suction filtration, pressure filtration, rotary filtration, sedimentation separation, or a combination thereof can be used.
[0044] <Drying process> Examples of drying equipment that can be used in the drying process of hexagonal boron nitride powder after solid-liquid separation include shelf dryers, fluidized bed dryers, spray dryers, rotary dryers, belt dryers, vacuum dryers, vibrating dryers, etc., or combinations thereof. The ambient temperature inside the dryer is preferably 50 to 300°C, more preferably 100 to 250°C. The drying time is not particularly specified, but it is preferable to dry until the moisture content approaches 0%, and generally, it is recommended to dry for 1 to 48 hours at the above temperature. Washing, solid-liquid separation, and drying may each be performed once, or they may be performed multiple times using the same method or a combination of different methods. During the drying process, boron nitride may undergo hydrolysis, resulting in a leached boron concentration exceeding 20 ppm. Vacuum drying is preferred as a drying method to suppress the hydrolysis of boron nitride.
[0045] <Classification process> Classification is preferable for the purpose of controlling the D95 of hexagonal boron nitride powder. The classification method is not particularly limited as long as the D95 can be controlled to a desired value or less, and known methods can be applied without restriction. Specifically, examples include vibrating sieves, wet sieves, wind classifiers, cyclones, liquid cyclones, etc. When applying wet classification, it is preferable to perform it before the drying process. [Examples]
[0046] The present invention will be explained below with reference to examples. In the following examples, the low-purity material before washing is labeled as nitride powder, and the high-purity material after washing is labeled as h-BN powder. Additionally, powders intended for seed crystals are indicated with (S).
[0047] <Cumulative distribution of volume-based particle size measured by laser diffraction and scattering methods> The particle size distribution of h-BN powder was measured using a Nikkiso Co., Ltd. MT3000 particle size distribution analyzer for samples prepared by the method described below, either unsonicated or sonicated. Ethanol was used as the solvent. The refractive index was set to 1.36 for ethanol and 1.74 for hexagonal boron nitride, and the measurement time was 30 seconds.
[0048] <Sample not treated with ultrasound> The measurement sample was prepared by adding 20 g of ethanol as a dispersion medium to a 50 mL screw-cap bottle and dispersing 1 g of h-BN powder in the ethanol.
[0049] <Sonicated sample> The measurement samples were ultrasonically treated using the method described below. First, 20 g of ethanol was added as a dispersion medium to a 50 mL screw-cap vial, and 1 g of h-BN powder was dispersed in the ethanol. Next, using a BRANSON ultrasonic homogenizer (SONIFIER SFX250), the tip (20 kHz microtip 1 / 4 inch) was placed 1 to 5 mm from the bottom of the screw-cap vial, and ultrasonic treatment was performed at an amplitude of 40% for 20 minutes. Then, the particle size distribution of the ultrasonically treated measurement samples was measured.
[0050] <Specific Surface Area> It was determined by the BET method (nitrogen adsorption one-point method) using a specific surface area analyzer (manufactured by Shimadzu Corporation: model FlowSorb 2-2300).
[0051] <MIU and MMD> MIU (dynamic friction coefficient) and MMD (variation value of dynamic friction coefficient) are dimensionless values measured using a friction tester (manufactured by Kato Tech Co., Ltd., product name: KES-SE). Specifically, h-BN powder was placed on artificial leather (manufactured by Idemitsu Techno Fine Co., Ltd., product name: Suplare PBZ13001 BK) simulating human skin at 0.5 mg / cm 2 and spread thinly to achieve the above amount, then the sensor unit (10 mm square silicon) of the friction tester was placed thereon, and MIU and MMD can be measured. The measurement conditions of the friction tester are set as: sensitivity: H, test table moving speed: 1 mm / sec, static load: 25 gf. The measurement is performed once. The sample preparation (spreading the h-BN powder on the artificial leather) and the measurement with the friction tester were repeated 5 times, and the average value of the 5 obtained measurement results was taken as the MIU and MMD of the h-BN powder.
[0052] <Preparation of BN Seed Crystal (Melamine 1)> A raw material mixture (S) was prepared by mixing 30 g of boron oxide (B2O3) as an oxygen-containing boron compound and 50 g of melamine as a nitrogen-containing organic compound in a ball mill. In the prepared raw material mixture (S), B / N was 0.36. Using a batch firing furnace for the prepared raw material mixture (S), in the heating step, the temperature was raised at a rate of 15°C / min under nitrogen gas flow, and the mixture was heated at a temperature of 1000°C for 10 hours to produce a nitrided powder (S). The prepared nitrided powder (S) was crushed with a stone mill type crusher, then acid-washed with a 5% hydrochloric acid aqueous solution, further filtered, washed with water, and dried to obtain h-BN powder (S) (Melamine 1).
[0053] <Preparation of BN Seed Crystal (Melamine 2)> A raw material mixture (S) was prepared by mixing 30 g of boron oxide (B2O3) as the oxygen-containing boron compound and 50 g of melamine as the nitrogen-containing organic compound in a ball mill. In the prepared raw material mixture (S), B / N was 0.36. Using a batch firing furnace for the prepared raw material mixture (S), in the heating step, the temperature was raised at 15°C / min under a nitrogen gas flow, and heating was performed at a temperature of 700°C for 10 hours to produce a nitrided powder (S). The prepared nitrided powder (S) was crushed with a stone mill type grinder, then acid-washed with a 5% hydrochloric acid aqueous solution, and further filtered, water-washed, and dried to obtain h-BN powder (S) (melamine 2).
[0054] <Preparation of BN seed crystal (melamine 3)> A raw material mixture (S) was prepared by mixing 30 g of boron oxide (B2O3) as the oxygen-containing boron compound and 50 g of melamine as the nitrogen-containing organic compound in a ball mill. In the prepared raw material mixture (S), B / N was 0.36. Using a batch firing furnace for the prepared raw material mixture (S), in the heating step, the temperature was raised at 15°C / min under a nitrogen gas flow, and heating was performed at a temperature of 1000°C for 6 hours to produce a nitrided powder (S). The prepared nitrided powder (S) was crushed with a stone mill type grinder, then acid-washed with a 5% hydrochloric acid aqueous solution, and further filtered, water-washed, and dried to obtain h-BN powder (S) (melamine 3).
[0055] <Preparation of BN seed crystal (melamine 4)> A raw material mixture (S) was prepared by mixing 50 g of boric acid (H3BO3) as the oxygen-containing boron compound and 50 g of urea as the nitrogen-containing organic compound in a ball mill. In the prepared raw material mixture (S), B / N was 0.49. Using a batch firing furnace for the prepared raw material mixture (S), in the heating step, the temperature was raised at 15°C / min under a nitrogen gas flow, and heating was performed at a temperature of 800°C for 10 hours to produce a nitrided powder (S). The prepared nitrided powder (S) was crushed with a stone mill type grinder, then acid-washed with a 5% hydrochloric acid aqueous solution, and further filtered, water-washed, and dried to obtain h-BN powder (S) (melamine 4).
[0056] <Preparation of BN seed crystals (reduction nitridation)> A raw material mixture (S) was prepared by mixing 50 g of boron oxide (B₂O₃) as the oxygen-containing boron compound, 8 g of calcium carbonate (CaCO₃) as the oxygen-containing alkaline earth metal compound, and 24 g of carbon black (C) as the carbon source compound in a ball mill. In the prepared raw material mixture, the B / C (molar ratio) was 0.72, and the CaO / B₂O₃ (molar ratio) was 0.11. Using a batch firing furnace for the prepared raw material mixture (S), in the heating step, the temperature was raised at a rate of 15°C / min under flowing nitrogen gas, and the mixture was heated at 1500°C for 6 hours to produce a nitrided powder (S). The prepared nitrided powder (S) was crushed with a stone mill type crusher, then acid-washed with a 5% hydrochloric acid aqueous solution, further filtered, washed with water, and dried to obtain h-BN powder (S) (reduction nitridation).
[0057] <Example 1> <Raw material mixture> A raw material mixture was obtained by mixing 50 g of boron oxide (B₂O₃) as the oxygen-containing boron compound, 8 g of calcium carbonate (CaCO₃) as the oxygen-containing alkaline earth metal compound, 25 g of carbon black (C) as the carbon source compound, and 40 g of the aforementioned seed crystals (Melamine 1) as the seed crystals in a ball mill. In the prepared raw material mixture, the B / C (atomic ratio) was 0.72, the CaO / B₂O₃ (molar ratio) was 0.11, and B S / C (atomic ratio) was 0.81.
[0058] <Reduction nitridation step> Using a batch firing furnace, the prepared raw material mixture was heated at 1500°C for 6 hours under flowing nitrogen gas, and then further heated at 1800°C for 2 hours to produce a nitrided powder. <Purification step> The prepared nitrided powder was acid-washed with a 5% hydrochloric acid aqueous solution, then filtered, washed with water, and vacuum-dried at 200°C to obtain h-BN powder.
[0059] <Classification step> The obtained h-BN powder was classified using a vibrating sieve with a mesh opening of 45 μm. Table 1 shows the average particle size (D50), (D90-D10) / D50, content of coarse particles exceeding 3 times D50, D95 of the h-BN powder mixture containing primary particles and secondary particles formed by agglomeration of the primary particles, the coefficient of dynamic friction (MIU), and the variation in the coefficient of dynamic friction (MMD) of the obtained h-BN powder.
[0060] <Preparing Powder Foundation> The obtained h-BN powder was mixed with the following cosmetic ingredients to prepare a cosmetic (powder foundation). (Ingredients) (Amount%) ·h-BN powder 20.0 • Mica 15.0 ·Synthetic Phlogopite 12.0 • Ethylhexyl methoxycinnamate 8.0 (Vinyl dimethicone / methicone silsesquioxane) crosspolymer 8.0 (Diphenyl Dimethicone / Vinyl Diphenyl Dimethicone / Silsesquioxane) Crosspolymer 8.0 Nylon 12, 3.0 Silica 3.0 Talc 3.0 • Acrylates crosspolymer 3.0 Perfluorooctyltriethoxysilane 3.0 Zinc oxide 3.0 • Polymethyl methacrylate polymer 3.0 • Silicone-treated red iron oxide (red iron oxide) 1.0 • Silicone-treated yellow iron oxide 0.6 • Silicone-treated black iron oxide 0.4 • Silicone-treated titanium dioxide 6.0
[0061] <Powder Foundation Review> Table 1 shows the results of our investigation into the smoothness, roughness, and moisturizing properties of the obtained powder foundations. The various properties described above were evaluated by having 20 panelists specializing in cosmetic evaluation use the present invention and comparative products. If less than 30% of the panelists felt the product was good, it was rated as ×; if 30% or more felt it was good, it was △; if 60% or more felt it was good, it was ○; and if 80% or more felt it was good, it was ◎.
[0062] <Example 2> h-BN powder was obtained using the same method as in Example 1, except that melamine 2 was used as the seed crystal. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0063] <Example 3> h-BN powder was obtained using the same method as in Example 1, except that melamine 3 was used as the seed crystal. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0064] <Example 4> In Example 1, h-BN powder was obtained using the same method as in Example 1, except that the composition ratio of the raw material mixture was changed as shown in Table 1, and the calcination temperature in the reduction nitriding process was changed as shown in Table 1. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0065] <Example 5> In Example 1, h-BN powder was obtained using the same method as in Example 1, except that the composition ratio of the raw material mixture was changed as shown in Table 1, and the calcination temperature in the reduction nitriding process was changed as shown in Table 1. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0066] <Example 6> h-BN powder was obtained using the same method as in Example 1, except that melamine 4 was used as the seed crystal. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0067] <Example 7> In Example 1, h-BN powder was obtained using the same method as in Example 1, except that the composition ratio of the raw material mixture was changed as shown in Table 1. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0068] <Comparative Example 1> h-BN powder was prepared under the same conditions as in Example 1, except that a seed crystal was not used. The preparation conditions and the properties of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0069] <Comparative Example 2> h-BN powder was produced under the same conditions as in Comparative Example 1, except that a sieve with a mesh opening of 90 μm was used in the classification process. The production conditions and the properties of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0070] <Comparative Example 3> h-BN powder was obtained using the same method as in Example 1, except that a seed crystal (reduced nitrided) obtained by the reduced nitriding method was used as the seed crystal. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0071] <Comparative Example 4> In Example 1, h-BN powder was obtained using the same method as in Example 1, except that the composition ratio of the raw material mixture was changed as shown in Table 1. The particle size distribution, coefficient of dynamic friction (MIU), and variation of the coefficient of dynamic friction (MMD) of the obtained h-BN powder are shown in Table 1. Furthermore, a powder foundation was prepared using the obtained h-BN powder in the same manner as in Example 1. The properties of the obtained powder foundation were evaluated using the same method as in Example 1. The results are shown in Table 1.
[0072] [Table 1]
[0073] As shown in Table 1, using the hexagonal boron nitride powder of the present invention in cosmetics resulted in high evaluations regarding smoothness, texture, and moisturizing properties.
Claims
1. In the volume-based cumulative distribution of particle size (a) measured by laser diffraction / scattering without ultrasonic treatment, the particle size of D95 is 70 μm or less, the coefficient of dynamic friction (MIU) is 0.50 or less, and the variation value of the coefficient of dynamic friction (MMD) is 0.005 or less. The D95 is the 95th percentile value of the volume-based cumulative distribution of particle size (a) in the particle size distribution curve. In the volume-based cumulative particle size distribution (b) measured by laser diffraction / scattering after ultrasonic treatment, the average particle size (D50) is 3 to 15 μm, (D90 - D10) / D50 is 1.30 or less, the content of coarse particles exceeding three times D50 is 2.0 volume% or less, and D10, D50, and D90 are the cumulative 10th percentile, 50th percentile, and 90th percentile values, respectively, in the volume-based cumulative particle size distribution (b) of the particle size distribution curve. A hexagonal boron nitride powder characterized by the following features.
2. Hexagonal boron nitride powder according to claim 1, for use in cosmetics.
3. A cosmetic composition comprising the hexagonal boron nitride powder described in claim 1 or 2.
Citation Information
Patent Citations
Boron nitride powder of turbostratic structure and its production
JP1998203807A
Method for manufacturing crystalline turbostratic structure boron nitride powder
JP2006232668A
Heat radiation member for lighting
JP2011225648A
Boron nitride powder, method for producing the same, composition containing the same, and heat dissipative material
JP2012111657A
Hexagonal boron nitride powder for cosmetic, method for producing the same and cosmetic
JP2012176910A